Pola Bahasa Perempuan Melawan Dominasi Laki-Laki melalui Konversasi dalam Talk Show Publik - Mahadi, Elly Manika Maya (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
This study aims to examine how women's language patterns challenge male dominance in conversations on the public talk show “Enaknya Jadi Laki-Laki”. The research employs the Membership Categorization Device method through conversation analysis. The findings reveal that women must first confront gender-based stereotypes before they can speak. In seeking equality, women often adopt masculine language patterns and draw upon commonly accepted cultural knowledge—actions that unintentionally, foster competition among women rather than directly challenging male dominance. It also finds that women tend to take on the role of facilitators in conversation, while men are more likely to assert their identity and self-image through denial or interruption. These dynamics reflect the complexities of gendered communication, underscoring the need for more effective language styles and structured settings in constructing gender discourse within public talk shows. This study highlights the importance of increasing female representation in media to enhance the visibility and legitimacy of women's perspectives.